Human rights, human dignity and justice: The Islamic perspective - Ansari, Abdul Haseeb; Salman, R. K. (Serials Publications, 2011)
For quite sometimes, there has been an impassioned debate as to whether human rights as encapsulated in the Universal Declaration of Human Rights is purely a ‘Western’ conception or is a universal conception and, this, applicable to all continents, regions and religions. This paper joins such debate and hypotheses that ‘human rights’ is a universal concept. It was there in all civilized societies and religions. It existed in Islam as early as the eightieth century. It continued and expanded in order to protect life, property, and dignity of man. Most of the human rights in Islam have the basis of the Divine wisdom; some others are man-made. The thesis is that human rights are well recognised in Islamic. On this premise, this paper considers the concept and magnitude of human rights in Islam. It analyses the sources of human right and examines various types of human rights in Islam. In doing so, it briefly discusses some prominent human rights, as perceived in Islam. It further stresses that human rights, human dignity and justice are one and the same which Islam preaches. This has been done to dispel a wrong premised belief that human rights do not exist in Islam; Islam emphasises more on duties. The paper concludes that since human rights or justice or human dignity is what Islam preaches, what remains is for the states that have proclaimed Islam as the religion of the state, to establish institutions that will ensure proper enforcement, protection and promotion of such rights. It, thus, suggests institutions like Wali-Mazalim and Hisbah